A Moving Dune, A Stunning View: Visitors’ Recollections of a Ranger-Led Hike at Indiana Dunes National Park - Forist, Brian E.; Merson, Martha; Allen, Louise C.; Hristov, Nickolay I. (Frontiers in Education, 2021)
Located 50 miles from Chicago, at Indiana Dunes National Park, thousands interact with rangers annually, many taking part in ranger-led hikes. The study focused on visitor recollections of a ranger-led hike that provided opportunities to learn about landscape change, recent events, and associated scientific findings. Interpreters are encouraged to co-construct audience-centered experiences, making space in interactions for visitors’ knowledge, interests, and previous experience. Researchers observed six ranger-led hikes incorporating audience-centered design elements and recruited a convenience sample of twenty-one visitors for participation in a pre-hike survey to gather responses about interest and knowledge before the hike and their willingness to participate in a follow up post-hike phone interview. After ranger-led hikes, researchers conducted fifteen interviews using a phenomenological approach to glean visitors’ recollections of the experience. Our findings confirm that visitors arrive with background knowledge, scientific interests, and curiosity. Months after the park experience, they were able to give examples of dune formation and change over time, the human effect on the landscape, and findings from recent events and scientific study at Mount Baldy. Interviewees recalled and reflected on rangers’ facilitation and use of props, as well as visual details and feelings evoked by the physical conditions. The results offer a rare look at what sticks with visitors after their participation in a ranger-led hike.